Plasma and salivary measures of testosterone and cortisol levels in basketball players under various games / training conditions, and nutritional strategies: an updated systematic review - Brini, Seifeddine; Clark, Cain C. T.; Ouergui, Ibrahim; Delextrat, Anne; Yagin, Fatma Hilal; Muscella, Antonella; Badicu, Georgian; Bouassida, Anissa; Clemente, Filipe Manuel; Al-Mhanna, Sameer Badri; Tabnjh, Abedelmalek Kalefh; Nobari, Hadi; et al. (Frontiers in Physiology, 2026)
BackgroundIn basketball research, hormonal monitoring has focused almost exclusively on plasma and salivary testosterone and cortisol, as these methods are more practical and accessible for applied sport settings than alternative approaches. Yet, no systematic review recapitulates these two methods together among Basketball players under various (games/training) conditions, and different nutritional strategies.ObjectivesThis systematic review synthesized the existing literature on testosterone and cortisol measurements in basketball players using salivary and blood samples under various (games/training) conditions, and different nutritional strategies, and discussed implications for practical monitoring.MethodsA comprehensive search of electronic databases (PubMed, Scopus, Web of Science, Google Scholar) was conducted for studies published between 1999 and 2025. Eligible studies involved basketball players and assessed testosterone and cortisol via salivary or blood sampling during training, matches, or recovery. Data were extracted and narratively synthesized due to heterogeneity and the absence of direct comparison studies.ResultsForty-two studies met the inclusion criteria. Salivary cortisol consistently reflected acute stress responses post-match, aligning closely with blood cortisol measures. Testosterone responses were more variable; salivary testosterone sometimes diverged from blood levels, indicating methodological sensitivity differences. The testosterone-to-cortisol ratio decreased following matches, highlighting a shift toward a catabolic state. Salivary sampling showed practical advantages for field monitoring but requires standardized protocols for testosterone assessment.ConclusionSalivary sampling is a promising, non-invasive alternative for monitoring cortisol in basketball players, with practical benefits for field use. However, discrepancies in salivary testosterone measurements compared to blood samples suggest cautious interpretation. The current literature lacks direct comparative studies in basketball, underscoring the need for future research to validate and standardize hormone monitoring methods to optimize training and recovery strategies.